Trends and challenges in gender research in engineering: Meta-analysis of CAL-Matilda contributions - Montoya-Noguera, Silvana; García de Cajén, Silvia; Villalba, Karen Beatriz; García Medina, María Angélica; Castillo, Sandra Patricia; Contreras-Ortiz, Sonia H. (LACCEI, 2024)
Research provides evidence and methodologies to evaluate the efficiency of actions in favor of gender equality in engineering. The Matilda and Women in Engineering Chair (CAL-Matilda) created the Research Committee (RC) to support these actions. This article focuses on grouping and analyzing the 36 publications of members of the RC in the first 3 years since the creation of the committee. The contributions consist of investigating the trends, challenges and opportunities in the promotion of gender equality in the engineering field in Latin America and the Caribbean. The findings show that adapting international models to local realities is crucial to achieve gender equality in STEM. The conclusions underline the importance of continuing to develop inclusive policies and programs that promote equality, suggesting that the next steps should focus on evaluating these long-term interventions and expanding successful strategies to other areas. These results highlight the relevance of continuing to research to support the decisions that promote gender equality in engineering in the region.